Research of Automatic Control Method of Swing Speed of Cutting Arm of Roadheader - GAO Feng; WANG Su-yu; GAO Juan; LI Rui; WU Miao (Gong-kuang zidonghua, 2011)
Because coal and rock in tunnelling roadway has phenomenon of sharp hardness change, so it's difficult to change swing speed of cutting arm of roadheader timely and effectively by manual control, then it will affect life of cutting head pick and cutting motor seriously. To solve the problem, the paper proposed an automatic control method of swing speed of cutting arm based on PID by analyzing relationship between swing speed v of cutting arm, cutting motor current I and hardness of coal and rock f, namely takes the difference of cutting motor rated current I0 and actual current I as input variable to control current I1 controlling valve port opening of electron-hydraulic proportional valve through linear combination of proportion unit, integration unit and differentiation unit, so as to control swing speed of cutting arm. The paper also proposed 5% control precision standard according to coal industry standard MT/T971-2005. The control method achieves aims of replacing artificial manipulation, protecting cutting head pick and cutting motor and makes cutting motor always work with full-load and constant power. Key words: